2009
DOI: 10.1002/ejoc.200900216
|View full text |Cite
|
Sign up to set email alerts
|

A Mild Approach to the Synthesis of 4‐Amino‐8‐(arylamino)pyrimido[5,4‐d]pyrimidine 3‐Oxides

Abstract: The reaction of benzylhydroxylamine with 6‐cyanopurines leads to the formation of 7‐benzyloxy‐8‐imino‐7,8‐dihydropyrimido[5,4‐d]pyrimidines. The hydrochloride of these compounds, isolated upon addition of aqueous hydrochloric acid, is a convenient precursor of the pyrimido[5,4‐d]pyrimidine N‐oxides when a suspension of the salt is refluxed in ethanol or acetonitrile. Refluxing a solution of the same salt in ethanol, leads to the Dimroth‐rearranged product.(© Wiley‐VCH Verlag GmbH & Co. KGaA, 69451 Weinheim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…6-Cyanopurines 1 had been previously used to generate 6-imidatopurines 6, 12 and reaction of these compounds with hydrazides was carried out in the presence of acid catalysis, aiming to prepare the 6-amidinopurines 4. Previous results on the reactivity of the purine ring, under basic conditions and in the presence of nucleophiles, indicated that attack on C8 was the major pathway, [8][9][10] leading to pyrimidopyrimidines 2. The use of a catalytic amount of sulfuric acid, when a suspension of compound 6a in dimethylsulfoxide was combined with acetic hydrazide 7a, prevented the competitive formation of product 2.…”
Section: Figure 1 a New Class Of Antitubercular Agentsmentioning
confidence: 99%
See 3 more Smart Citations
“…6-Cyanopurines 1 had been previously used to generate 6-imidatopurines 6, 12 and reaction of these compounds with hydrazides was carried out in the presence of acid catalysis, aiming to prepare the 6-amidinopurines 4. Previous results on the reactivity of the purine ring, under basic conditions and in the presence of nucleophiles, indicated that attack on C8 was the major pathway, [8][9][10] leading to pyrimidopyrimidines 2. The use of a catalytic amount of sulfuric acid, when a suspension of compound 6a in dimethylsulfoxide was combined with acetic hydrazide 7a, prevented the competitive formation of product 2.…”
Section: Figure 1 a New Class Of Antitubercular Agentsmentioning
confidence: 99%
“…11 Furthermore, our studies on the reactivity of the pyrimidopyrimidine derivatives 2 (R 2 = OBn) have proved that the conversion of 2 (R 2 = OBn) into 3 (R 2 = OBn) occurs efficiently under acid conditions although other products may also be formed (Scheme 1). 10 In the present work, compounds 2 were considered to be convenient precursors of the aromatic pyrimido[5,4-d]pyrimidines 3 (R 2 = NHCOR 3 ).Scheme 1 Synthesis of 2, its conversion into 3 (R 2 = OBn) and attempts to generate new derivatives 3 (R 1 = 4-NCC 6 H 4 , R 2 = NHCOR 3 ).Herein we report our attempts to convert pyrimido[5,4-d]pyrimidine 2 (R 2 = NHCOR 3 ) into 3 (R 2 = NHCOR 3 ) and the new synthetic strategy designed to generate derivatives 3 starting from 6-carbohydrazonamidepurines 4 that have proved to be valuable precursors for the target compounds 3. Compound 2 (R 1 = 4-NCC 6 H 4 , R 2 = NHCOPh) was prepared by reaction of the 6-cyanopurine 1 (R 1 = 4-NCC 6 H 4 ) with benzoic hydrazide according to a previously described procedure.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…13 Also, reaction of 9-cyanopurines with O-benzylhydroxylamine or isoniazide resulted in the formation of pyrimidopyrimidines. 14,15 Recently, an efficient method for the synthesis of aromatic 4-acylhydrazido-8-arylaminopyrimidopyrimidine derivatives has been published. 16 The [4 + 2] cycloaddition reactions of 6-[(dimethylamino)methylene]amino uracil with various in situ-generated imine glyoxylates or imine oxides provided Synthesis, characterisation, and in vitro antibacterial evaluation of a new class of 2-substituted-4-methyl-7,8-dihydro-5H-pyrimido [4,5-d]thiazolo[3,2-a] pyrimidines…”
mentioning
confidence: 99%